Primary Hodgkin lymphoma of the central nervous system: Two case reports and review of the literature. Issue 6 (27th March 2013) - Kresak, Jesse Lee; Nguyen, Johnny; Wong, Kondi; Davis, Richard
<x xml:space="preserve">Abstract</x> CNS involvement by systemic Hodgkin lymphoma (HL) is quite rare, but the disease limited to the CNS is an exceptionally rare entity. The incidence of CNS‐HL has been estimated at 0.2–0.5% of cases, but a more recent study has modified that figure to less than 0.02%. Like the conventional form, the diagnosis of primary CNS‐HL rests upon distinct morphological and immunohistochemical characteristics, including diagnostic Reed‐Sternberg cells, in addition to staging studies demonstrating a lack of disease elsewhere. The paucity of cases in the literature precludes reliable clinical and demographic data, as well as a consensus on treatment and prognosis. We present two cases of primary cerebellar HL, one with 10‐year follow‐up, and a relevant review of the literature.